Patriarchal Moments Reading Patriarchal Texts - Cuttica, Cesare; Mahlberg, Gaby (Textual Moments in the History of Political Thought, 2015)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Patriarchalism is omnipresent in Western culture and it pervades the texts that have shaped this culture. From the creation story in the Bible to the ancient authors, from the Church fathers to the treatises of Enlightenment philosophers, right up to modern fiction, male authority over women, children and other dependents has shaped the nature of human relationships and the discourses about these relationships. This collection of short essays offers fresh and novel readings of key texts in the history of patriarchalism as a concept of power. The texts selected are from political, religious and literary works and together the readings add new insights to a tradition that has never gone uncontested, yet is unlikely to disappear soon.